The Behaviour of Magnetized Strange Quark Matter on Bianchi V Ih Universe in the Framework of f(R,T) Theory - , Sezgin Aygün; , Can Aktaş; , İhsan Yılmaz (Archives of Current Research International, 2017)
In this paper we have investigated Bianchi V Ih universe model with magnetized strange quark matter (MSQM) distribution in f (R,T) gravity. For the solutions of modified field equations we have used the EoS of strange quark matter and anisotropy parameter with α = 1,-1,0 in Bianchi V Ih universe. We get magnetic field for α = -1 parameter but we obtain h2 = 0 for α = 1 and α = 0 parameters in Bianchi V Ih models. At the end of time, we get dark energy model for α = 1 and α = 0 models i.e. we get ρ = -p = Bc. We conclude that the source of cosmological !term may be SQM i.e. the source of dark energy may be SQM. These results agree with the solutions of Aktaş and Aygün also Aygün et al. in f (R,T) theory. Also, we get magnetized strange quark matter distribution in Einstein’s general relativity theory with ∧ for this model.